An overview of the current management of chronic obstructive pulmonary disease: can we go beyond the GOLD recommendations?. (2nd January 2018) - Cazzola, Mario; Rogliani, Paola; Puxeddu, Ermanno; Ora, Josuel; Matera, Maria Gabriella
ABSTRACT: Introduction : Treatment recommendations are based on randomized controlled trials (RCTs). However, only about 1 in 20 people meet the inclusion criteria for RCTs forming consensus guidelines in chronic obstructive pulmonary disease (COPD). Consequently, the one-size-fits-all approach focused merely on traditional symptoms and risk of exacerbations is inadequate to treat COPD. COPD needs a personalized medicine strategy because of the relevance of COPD heterogeneity for subject-based health risk assessment and stratification in the clinical arena. Areas covered : Since the therapeutic approach proposed by the 2017 GOLD report takes no account of COPD heterogeneity, the advances with the current pharmacological options and the different approaches focused on phenotypes of COPD that can be used in an attempt to respond to unmet therapeutic needs are reviewed. Expert commentary : The one-size-fits-all approach that focuses solely on traditional symptoms and risk of exacerbations is inadequate to treat COPD. COPD needs a personalized medicine strategy because of the relevance of COPD heterogeneity. Phenotyping provides potential for a more personalized approach than the former model of care because it allows clustering patients defined by clinical characteristics and sharing common clinical outcomes. However, it is still too much of a simplistic method that, in any case, must be validated in future clinical studies.